2013
DOI: 10.1051/epjconf/20135301004
|View full text |Cite
|
Sign up to set email alerts
|

Connecting accelerator experiments and cosmic ray showers

Abstract: Abstract. Currently the uncertainty in the prediction of shower observables for different primary particles and energies is dominated by differences between hadronic interaction models. The LHC data on minimum bias measurements can be used to test Monte Carlo generators and these new constrains will help to reduce the uncertainties in air shower predictions. In this article, after a short introduction on air showers we will show the results of the comparison between the updated version of high energy hadronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Specific predictions are then performed using different air showers simulation codes, such as AIRES [13] or CORSIKA [14], which incorporate different models to describe the hadronic interactions, such as QGSJET [15], EPOS [16] or SIBYLL [17], which were developed with emphasis in air shower physics. These models predict the main features of the interactions and are regularly updated [18,19] in order that they better account for the measurements performed at high energy hadron colliders, such as the 3 A more accurate estimate of the pion decay energy can be performed [11] using that the density of the atmosphere is approximately exponential, with ρ(z) = ρ 0 exp(−z/h 0 ), with h 0 ≃ 10 km. One has then that ρ(z) = X cos θ/h 0 for a shower with zenith θ after traversing a slant depth X.…”
Section: The Physics Of Air Showersmentioning
confidence: 99%
“…Specific predictions are then performed using different air showers simulation codes, such as AIRES [13] or CORSIKA [14], which incorporate different models to describe the hadronic interactions, such as QGSJET [15], EPOS [16] or SIBYLL [17], which were developed with emphasis in air shower physics. These models predict the main features of the interactions and are regularly updated [18,19] in order that they better account for the measurements performed at high energy hadron colliders, such as the 3 A more accurate estimate of the pion decay energy can be performed [11] using that the density of the atmosphere is approximately exponential, with ρ(z) = ρ 0 exp(−z/h 0 ), with h 0 ≃ 10 km. One has then that ρ(z) = X cos θ/h 0 for a shower with zenith θ after traversing a slant depth X.…”
Section: The Physics Of Air Showersmentioning
confidence: 99%
“…Second, the retuning of the cosmic-rays hadronic MCs using LHC data supports a mixed composition of proton and heavier ions (α particles and/or iron) at the tail of the cosmic ray spectrum up to E CR ∼10 20 eV, with reduced model uncertainties (from ∼50 g/cm 2 to ∼20 g/cm 2 for the values of the X max shower maximum in the atmosphere) [11]. Upcoming LHC data studies will also help to solve the current disagreement between the observed and predicted number of muons at ground for the highest-energy showers.…”
Section: Discussionmentioning
confidence: 67%
“…Around the GZK cutoff, the CR data prefer a mixed proton-iron composition (Fig. 2, right), with reduced model uncertainties (from ∼50 g/cm 2 to ∼20 g/cm 2 for values of X max where the proton-iron difference is about 100 g/cm 2 ) [11].…”
Section: Epj Web Of Conferencesmentioning
confidence: 93%
See 1 more Smart Citation
“…Then, the models used for shower simulation extrapolate low energy data taken from accelerator experiments by several orders of magnitude in order to reach the energy of the cosmic rays. Note that, at present, the hadronic interaction models are being updated in order to reproduce the Large Hadron Collider data, which reaches up to cosmic ray energies of the order of ∼ 2 × 10 16 eV (E cm = 7 TeV) [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%